Pendampingan Pembuatan Media Ajar Berbasis ICT “ Kahoot” Bagi Guru MI Mambaul Ulum Candipari - Mufidah, Eli; Ningseh, Wiwik Rahayu (TAAWUN, 2022)
Due to the lack of variety of ICT media used in learning, researchers provided assistance to the Madrasah Ibtidaiyah Mambaul Ulum Candipari, this assistance was to provide understanding and awareness to teachers of the importance of using ICT-based teaching media "Kahoot" and Improve the quality and skills of teachers in using ICT-based technology applications (Kahoot) to teach students remotely so that interest and learning outcomes increase. The research method used is descriptive qualitative method. Based on the results of this PKM implementation, there are 8 out of 10 teachers who are able to make ICT-based Teaching Media "Kahoot" or 80% of teachers who are able to make ICT-based Teaching Media "Kahoot". And there is 2 teacher or 20% who has not been able to make Teaching Media using Kahoot. This happens because teachers still have difficulty using technology and are still using Kahoot for the first time as an application to create Teaching Media. This research and assistance has succeeded in opening up the insight of teachers and developing teacher abilities in making learning media at MI Mambaul Ulum Candipari. The teachers have been able to develop interactive media using Kahoot with various themes contained in the 2013 curriculum. For this reason, this activity can provide benefits in increasing teacher development, creativity and awareness of the importance of media in learning.